Current clinical criteria for Lynch syndrome are not sensitive enough to identify MSH6 mutation carriers. Issue 9 (28th June 2010) - Sjursen, Wenche; Haukanes, Bjørn Ivar; Grindedal, Eli Marie; Aarset, Harald; Stormorken, Astrid; Engebretsen, Lars F; Jonsrud, Christoffer; Bjørnevoll, Inga; Andresen, Per Arne; Ariansen, Sarah; Lavik, Liss Anne S; Gilde, Bodil; et al.
Abstract : Background: Reported prevalence, penetrance and expression of deleterious mutations in the mismatch repair (MMR) genes, MLH1, MSH2, MSH6 and PMS2, may reflect differences in the clinical criteria used to select families for DNA testing. The authors have previously reported that clinical criteria are not sensitive enough to identify MMR mutation carriers among incident colorectal cancer cases. Objective: To describe the sensitivity of the criteria when applied to families with a demonstrated MMR mutation. Methods: Families with an aggregation of colorectal cancers were examined for deleterious MMR mutations according to the Mallorca guidelines. All families with a detected MMR mutation as of November 2009 were reclassified according to the Amsterdam and Bethesda criteria. Results: Sixty-nine different DNA variants were identified in a total of 129 families. The original Amsterdam clinical criteria were met by 38%, 12%, 78% and 25% of families with mutations in MSH2, MSH6, MLH1 and PMS2, respectively. Corresponding numbers for the revised Amsterdam criteria were 62%, 48%, 87% and 38%. Similarly, each of the four clinical Bethesda criteria had low sensitivity for identifying MSH6 or PMS2 mutations. Conclusion: Amsterdam criteria and each of the Bethesda criteria were inadequate for identifying MSH6 mutation-carrying kindreds. MSH6 mutations may be more common than currently assumed, and the penetrance/expression of MSH6 mutations, as derived from families meeting current clinical criteria, may be misleading. To increase detection rate of MMR mutation carriers, all cancers in the Lynch syndrome tumour spectrum should be subjected to immunohistochemical analysis and/or analysis for microsatellite instability.